PENGARUH METODE LATIHAN TARGET POINT TERHADAP KETEPATAN SMASH DALAM PERMAINAN BULUTANGKIS PADA ATLET PB UNJA SMART - Muhammad Azan Zidan; Sukendro; Yusradinafi; Ely Yuliawan; Palmizal A.; Mohd. Adrizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Target Point training method on the accuracy of smashes in PB UNJA SMART athletes. Accurate smashes play an important role in the effectiveness of attacks, but initial observations indicate that the accuracy of athletes' smashes has not yet achieved the expected results. Therefore, a more focused training method is needed on shuttlecock control and target focus, one of which is through the application of the Target Point method. This study used an experimental method with a One-Group Pretest–Posttest design. The sample consisted of 10 athletes determined through a total sampling technique. The research instrument was a smash accuracy test with 30 trials with the target point as the target. Data were analyzed using descriptive statistics and the inferential Paired Sample t-Test using SPSS version 26.0. The normality test showed that the data were normally distributed, so parametric analysis could be performed. The results showed an increase in smash accuracy after being given Target Point training. The average pretest score of 13.90 increased to 22.20 in the posttest. The results of the Paired Sample t-Test showed a significance value of 0.000 (<0.05), thus concluding that the Target Point method significantly improved the accuracy of athletes' smashes. Therefore, this method can be used as an alternative training program to improve smash accuracy.